2011
DOI: 10.1299/jsdd.5.30
|View full text |Cite
|
Sign up to set email alerts
|

Steering Law of Control Moment Gyros using Optimization of Initial Gimbal Angles for Satellite Attitude Control

Abstract: Control Moment Gyroscope (CMG) has been expected to be applied to a spacecraft such as an earth observation satellite in recent years. However it is not easy to control it because CMG has a singularity condition and a major source of disturbance. Although there are many singularity avoidance logics, these optimal methods from the viewpoint of singularity avoidance may cause inner disturbance by fast and furious motion of gimbals in avoiding singularity. This paper presents a new but simple CMG steering law usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Nanamori [22] expanded on the work of Wie to implement preferred gimbal angles to multiple target collection. These preferred gimbal angles were only set at the beginning of the multiple target mission for the first target.…”
Section: • Applied Optimizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Nanamori [22] expanded on the work of Wie to implement preferred gimbal angles to multiple target collection. These preferred gimbal angles were only set at the beginning of the multiple target mission for the first target.…”
Section: • Applied Optimizationmentioning
confidence: 99%
“…Following the work of Wie, Nanamori [22] developed a method of optimizing initial SGCMG gimbal angles prior to a multiple target agile s/c trajectory mission. Nanamori recognized that a SR method of solving the torque equation can cause chatter in the gimbals as the algorithm attempts to navigate past a singularity.…”
Section: Multiple Target Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature [3,4], it is assumed that gimbals are positioned at desirable initial angles using solo null motion, namely, a state where gimbals produce no net torque on the spacecraft. Vadali et al [3] demonstrated the existence of "preferred sets of initial gimbal angles" that avoid singularities, accomplishing singularity-free steering by using a simple pseudo inverse law with initial null motion to position gimbals at their preferred angles.…”
Section: Introductionmentioning
confidence: 99%